Gambaran Epidemiologi Penderita Demam Berdarah Dengue (DBD) Di Rumah Sakit Umum Sundari Medan Tahun 2016 - Hertati Pasaribu; Fazidah A Siregar; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACT Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus through Aedes aegypti mosquito bites. Medan city is one of the areas categorized as endemic in North Sumatera Province. In 2013 there are 1,270 cases with 0.7% Case Fatality Rate (CFR) in-crease in 2014 with 1,699 cases and CFR 0.9%. In RSU Sundari Medan in 2015 as many as 297 cases and 338 cases in 2016. The aims to identify the epidemiology of DHF patients at Sundari General Hospital Medan in 2016. This is a descriptive study with case series design. Population of this research is 338 data and 183 samples of data DHF patients using Simple Random Sampling. Statistical analysis use Exact Fisher, Chi-Square, Kruskal Wallis, Kolmogorov Smirnov, and Mann-Whitney. The result shows that the largest proportion of DHF patients was 15-24 years old (24,6%), male (54.1%), Islam (89,1%), senior high school (29.5%), student (32,8%), from Medan (94,0%), time is December (12.6%), platelet count at hospital ≤100.000/mm3 (55,2%), platelet count when out of hospital >100.000/mm3 (78,7%), percentage of hematocrit at hos-pital <20% (73,8%), percentage hematocrit when out of hospital <20% (95,6%), grade I (86.3 %), average length of stay 5,14 days, recovery (76,0%), source of cost is not own expense (83,1%). There was no significant difference in severity based on age, the severity based on the condition when returned. There was a significant difference in proportion between platelet when out of hospital based on platelet when first day in hospital, hematocrit when out of hospital based on hematocrit when first day in hospital, the average length of stay based on the condition when returned, the average length of stay based on the source of cost. It was suggested that RSU Sundari Medan should improve the quality of service to people and can anticipate if there is an increase of DHF patients. Keywords : DHF, Patient Epidemiology, Sundari General Hospital